Multifunctional, Superelastic, and Lightweight MXene/Polyimide Aerogels - Liu, Ji; Zhang, Hao‐Bin; Xie, Xi; Yang, Rui; Liu, Zhangshuo; Liu, Yafeng; Yu, Zhong‐Zhen (Small (Weinheim an der Bergstrasse, Germany), 2018)
2D transition metal carbides and nitrides (MXenes) have gained extensive attention recently due to their versatile surface chemistry, layered structure, and intriguing properties. The assembly of MXene sheets into macroscopic architectures is an important approach to harness their extraordinary properties. However, it is difficult to construct a freestanding, mechanically flexible, and 3D framework of MXene sheets owing to their weak intersheet interactions. Herein, an interfacial enhancement strategy to construct multifunctional, superelastic, and lightweight 3D MXene architectures by bridging individual MXene sheets with polyimide macromolecules is developed. The resulting lightweight aerogel exhibits superelasticity with large reversible compressibility, excellent fatigue resistance (1000 cycles at 50% strain), 20% reversible stretchability, and high electrical conductivity of ≈4.0 S m−1. The outstanding mechanical flexibility and electrical conductivity make the aerogel promising for damping, microwave absorption coating, and flexible strain sensor. More interestingly, an exceptional microwave absorption performance with a maximum reflection loss of −45.4 dB at 9.59 GHz and a wide effective absorption bandwidth of 5.1 GHz are achieved. A 3D, electrically conductive, mechanically strong, and flexible MXene‐based aerogel reinforced with polyimide is fabricated for the first time. The conductive MXene/polyimide aerogel shows superelasticity, excellent resistance to fatigue for 1000 compression cycles under 50% strain, and thermal stability and fire retardancy, demonstrating its potential applications as multifunctional strain sensors and high‐performance microwave absorption coatings.